Mengevaluasi Mata Uang Kripto sebagai Properti: Sebuah Studi tentang Keberadaan Digitalnya dan Klasifikasi Hukum Syariah dalam Fiqh al-Muʿāmalāt Kontemporer - Muhammad Abduh Tuasikal; Jaih Mubarak; Ibdalsyah; Yulizar Djamaluddin Sanrego (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The development of blockchain technology has led to the emergence of cryptocurrency as a new form of digital property. This has sparked discussions regarding its legal status and suitability as an object of muʿāmalah (transactions) within Islamic jurisprudence. The lack of a physical form (al-wujūd al-ḥissī) in crypto-assets raises questions about whether these digital entities meet the criteria for al-māl (property) as defined by Sharīʿah. This study aims to evaluate the legal status of cryptocurrency by examining its digital existence (al-wujūd al-ḥukmī). Furthermore, it assesses cryptocurrency’s compliance with classical fiqh principles and contemporary accounting standards. The research employs a qualitative methodology, utilizing a descriptive-analytical, library-based approach. The analysis integrates classical fiqh criteria—such as taqawwum (value), intifāʿ (benefit), imkān al-taslīm (possibility of delivery), and ḍamān (guarantee)—with asset-recognition parameters found in IFRS and US-GAAP, including identifiability, control, and future economic benefits. Data were gathered from fiqh literature, academic publications on crypto-assets, and international accounting standards. The findings indicate that cryptocurrency possesses legal existence (al-wujūd al-ḥukmī) through mechanisms of digital control, blockchain verification, and its ability to be reliably owned, transferred, and measured. These characteristics fulfill the essential elements of property in fiqh, particularly utility, transferability, and the guarantee of value. Additionally, the adoption of cryptocurrency offers socio-economic benefits, including financial inclusion, more efficient remittances, individual economic empowerment, and increased transactional transparency.